Exchange of endogenous and heterogeneous yeast terminators in Pichia pastoris to tune mRNA stability and gene expression. Issue 22 (1st December 2020) - Ito, Yoichiro; Terai, Goro; Ishigami, Misa; Hashiba, Noriko; Nakamura, Yasuyuki; Bamba, Takahiro; Kumokita, Ryota; Hasunuma, Tomohisa; Asai, Kiyoshi; Ishii, Jun; Kondo, Akihiko
Abstract: In the yeast Saccharomyces cerevisiae, terminator sequences not only terminate transcription but also affect expression levels of the protein-encoded upstream of the terminator. The non-conventional yeast Pichia pastoris (syn. Komagataella phaffii ) has frequently been used as a platform for metabolic engineering but knowledge regarding P. pastoris terminators is limited. To explore terminator sequences available to tune protein expression levels in P. pastoris, we created a 'terminator catalog' by testing 72 sequences, including terminators from S. cerevisiae or P. pastoris and synthetic terminators. Altogether, we found that the terminators have a tunable range of 17-fold. We also found that S. cerevisiae terminator sequences maintain function when transferred to P. pastoris . Successful tuning of protein expression levels was shown not only for the reporter gene used to define the catalog but also using betaxanthin production as an example application in pathway flux regulation. Moreover, we found experimental evidence that protein expression levels result from mRNA abundance and in silico evidence that levels reflect the stability of mRNA 3′-UTR secondary structure. In combination with promoter selection, the novel terminator catalog constitutes a basic toolbox for tuning protein expression levels in metabolic engineering and synthetic biology in P. pastoris .